Visualisation of PCNA monoubiquitination in vivo by single pass spectral imaging FRET microscopy. - Christopher Batters; Hannah Zhu; Julian E Sale (PLoS ONE)
Monoubiquitination of the DNA sliding clamp, PCNA, plays a central role in the control of damage bypass during replication. By combining a widely-spaced FRET donor/acceptor pair (CFP and mRFP) with spectral imaging, we have developed a simple method for the visualisation of PCNA monoubiquitination in both fixed and live cells with a single imaging pass. We validate the method with genetic controls in the avian cell line DT40 and use it to examine the intracellular dynamics of PCNA ubiquitination following subnuclear UV irradiation. This general approach is likely to be of utility for live imaging of post-translational modifications of a wide range of substrates in vivo.